2015
DOI: 10.1039/c5ra10576e
|View full text |Cite
|
Sign up to set email alerts
|

Mineral carbonation of a desulfurization residue for CO2 sequestration

Abstract: The feasibility of mineral carbonation of a desulfurization residue for sequestering CO 2 was evaluated both through theoretical and experimental approaches. The carbonation reaction, including carbonation of Ca(OH) 2 and CaSO 4 , occurred through a kinetically controlled stage with an activation energy of 20.21 kJ mol À1 . The concentration of ammonia, CO 2 flow rate, liquid to solid ratio and temperature impacted on the carbonation ratio of the desulfurization residue through their direct and definite influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Also the reduction in the newly created pores and the replacement of TEPA on the outer nanotube surface, instead of their inner surface, proposed an increase in the average pore size. From Figure b it can be seen that the nanocomposite pore size is concentrated in the range of 2–10 nm. , …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Also the reduction in the newly created pores and the replacement of TEPA on the outer nanotube surface, instead of their inner surface, proposed an increase in the average pore size. From Figure b it can be seen that the nanocomposite pore size is concentrated in the range of 2–10 nm. , …”
Section: Resultsmentioning
confidence: 91%
“…From Figure 6b it can be seen that the nanocomposite pore size is concentrated in the range of 2−10 nm. 41,42 In addition, a comparison of CO 2 adsorption studies with the current work was presented in Table 2. At the top of the table, a variety TEPA/PEI-based adsorbents were shown whose synthesis process is often costly and complex.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the properties of MMT, the pillaring process is often performed, which involves exchanging the interlayer cations with organic or inorganic cations. Various mineral composite materials are used widely in catalysis, energy storage, and wastewater treatment together with supporting minerals such as kaolinite [26][27][28], halloysite [29][30][31][32][33][34], attapulgite [35][36][37], talc [38], expanded perlite [39], and tailings [40][41][42]. MoS 2 and most MoS 2 composites are hydrophobic and cannot be dispersed in water.…”
Section: Nano Resmentioning
confidence: 99%
“…The choices of most researchers for support materials in preparation of CO 2 adsorbents have been metal–organic frameworks (MOFs), , mesoporous carbon, resins, mesoporous silica, aerogel, macroporous silica, MCM-41, , TiO, and SBA-15. , Research has shown that clays, due to the presence of several clay minerals and some impurities in their structure, and on the other hand, due to having features such as low cost, high mechanical stability, and high chemical stability, can be used in more advanced applications and in the role of supporting materials in solid base adsorbents by changing and improving the structure. ,, In the application of nanoclays as effective adsorbents, Pham et al studied the increase of CO 2 adsorption using nanozeolite synthesis. The results showed a very high concentration of nanozeolite at ambient temperature, and adsorption capacity dropped by 6.33% after 10 regeneration cycles.…”
Section: Introductionmentioning
confidence: 98%